Sulfur atom doped coal pitch-based carbon aerogel, preparation method and application

By doping sulfur atoms in coal asphalt-based carbon aerogels and carbohydrate pyrolysis treatment, the problem of impedance matching imbalance of pure carbon aerogel materials is solved, and the optimization of electromagnetic wave absorption performance and the improvement of multiple characteristics of the material is achieved.

CN119706790AActive Publication Date: 2025-03-28CHINA COAL (SHENZHEN) RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411882186.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Existing pure carbon aerogel materials have impedance matching imbalance in the field of electromagnetic wave absorption and cannot be directly used to prepare electromagnetic absorbing materials.

Method used

By doping sulfur atoms in coal asphalt-based carbon aerogels and combining the amount of sulfur-containing materials to regulate the carbonization pyrolysis treatment method, sulfur atom-doped coal asphalt-based carbon aerogel microspheres were prepared.

Benefits of technology

It realizes the impedance matching of the material and the optimization of electromagnetic wave absorption performance, and has the characteristics of "width, strong, light and thin", which significantly improves the attenuation ability of electromagnetic waves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706790A_ABST
    Figure CN119706790A_ABST
Patent Text Reader

Abstract

The invention discloses sulfur atom doped coal pitch-based carbon aerogel, a preparation method and application. The preparation method comprises the following steps: dissolving coal pitch in a solvent, adding a cross-linking agent and a catalyst, uniformly mixing to obtain a pitch mixed solution, heating the pitch mixed solution for reaction, washing and drying to obtain coal pitch-based aerogel microspheres; uniformly mixing the coal pitch-based aerogel microspheres with a sulfur-containing material according to a mass ratio of (0.1-5): 1 to obtain a carbonized precursor; and performing carbonization pyrolysis treatment on the carbonized precursor in an oxygen-free atmosphere to obtain the sulfur atom doped coal pitch-based carbon aerogel microspheres. The prepared material is applied to the field of electromagnetic wave absorption. The invention provides an innovative technical path for preparing a material with excellent electromagnetic wave attenuation performance through a method of combining regulation and control of the dosage of the sulfur-containing material and doping of sulfur atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electromagnetic wave absorbing materials, and in particular relates to a sulfur atom-doped coal tar pitch-based carbon aerogel, a preparation method and an application thereof. Background Art

[0002] With the advancement of modern science and technology, electronic and electrical equipment are widely used in society. However, the electromagnetic radiation and interference generated by electronic and electrical equipment during operation have become the fourth largest environmental pollution problem after air pollution, water pollution and noise pollution, which has had a serious impact on people's production and life, especially in the field of precision electronic instruments in the medical field, communication systems in the field of aerospace, and the security of key information in network communications. Among the common absorbing materials, carbon materials (such as carbon fiber, carbon nanotubes, carbon aerogel, etc.) have important research and application value in the field of electromagnetic wave absorption due to their excellent electromagnetic wave absorption performance and light weight and high strength.

[0003] At present, pure carbon aerogel materials prepared with coal tar pitch as the carbon source can effectively promote multiple emission and attenuation of electromagnetic waves inside the material due to their extremely low density and large specific surface area, thereby significantly enhancing the attenuation effect of electromagnetic waves, and have the possibility of becoming electromagnetic absorption materials. However, the high conductivity of pure carbon aerogel may cause impedance matching imbalance and cannot be directly used to prepare electromagnetic absorption materials. The present invention dopes sulfur atoms on the basis of coal tar-based carbon aerogel, in order to achieve the optimization of impedance matching and electromagnetic wave absorption performance of carbon aerogel materials. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a sulfur atom-doped coal tar pitch-based carbon aerogel, a preparation method and an application. By combining the method of regulating the amount of sulfur-containing materials and sulfur atom doping, an innovative technical path is provided for preparing materials with excellent electromagnetic wave attenuation performance.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0006] In the first aspect of the present invention, the present invention proposes a method for preparing sulfur atom-doped coal pitch-based carbon aerogel, as follows:

[0007] (1) dissolving coal tar pitch in a solvent, adding a crosslinking agent and a catalyst, and mixing them uniformly to obtain an asphalt mixed solution, heating the asphalt mixed solution for crosslinking reaction, and washing and drying to obtain coal tar pitch-based aerogel microspheres;

[0008] (2) uniformly mixing the coal tar pitch-based aerogel microspheres and the sulfur-containing material to obtain a carbonized precursor;

[0009] Wherein, the mass ratio of sulfur-containing material to coal tar pitch-based aerogel microspheres is (0.1-5):1;

[0010] (3) The carbonized precursor is subjected to carbonization pyrolysis treatment in an oxygen-free atmosphere to obtain sulfur-doped coal tar pitch-based carbon aerogel microspheres.

[0011] Preferably, in step (1), the solvent comprises one or more of toluene, acetic acid, carbon disulfide, carbon tetrachloride and cyclohexane.

[0012] Preferably, the ratio of the solvent volume to the coal tar pitch mass is 1 to 15 mL / g.

[0013] Preferably, the crosslinking agent comprises one or more of glyoxal, terephthalaldehyde, terephthalenediol and furfural.

[0014] Preferably, the ratio of the volume of the cross-linking agent to the mass of the coal tar pitch is 5 to 15 mL / g.

[0015] Preferably, the catalyst comprises one or more of concentrated sulfuric acid, anhydrous aluminum chloride, anhydrous zinc chloride and sodium methoxide.

[0016] Preferably, the mass ratio of the catalyst to the coal tar pitch is 0.005-0.08, that is, the mass of the catalyst accounts for 0.5-8% of the mass of the coal tar pitch.

[0017] Preferably, in step (1), the temperature of the cross-linking reaction is 50 to 80° C., and the reaction time is 24 to 216 hours.

[0018] Preferably, in step (1), the washing reagent includes one or both of water and ethanol; the drying temperature is 50 to 160° C., and the drying time is 3 to 32 hours.

[0019] Preferably, in step (2), the sulfur-containing material includes one or more of elemental sulfur, sulfite and organic sulfur compound.

[0020] More preferably, the sulfur-containing material includes one or more of sublimated sulfur, sodium sulfite, thioacetamide and thiourea.

[0021] Preferably, in step (3), the temperature of carbonization pyrolysis is 800-1600° C., and the time of carbonization pyrolysis is 60-180 min.

[0022] More preferably, in step (3), the heating rate of the carbonization pyrolysis process is controlled to be 2 to 5°C / min.

[0023] In a second aspect of the present invention, the present invention provides a sulfur atom-doped coal pitch-based carbon aerogel, which is prepared by the above-mentioned preparation method.

[0024] In the third aspect of the present invention, the present invention proposes an application of sulfur atom-doped coal tar pitch-based carbon aerogel, and the prepared sulfur atom-doped coal tar pitch-based carbon aerogel is made into an electromagnetic wave absorbing material for use in the field of electromagnetic wave absorption.

[0025] Beneficial effects:

[0026] The sulfur atom-doped coal tar pitch-based carbon aerogel microsphere material of the present invention has a large specific surface area, a small tap density, and suitable impedance matching, thereby realizing the "wide, strong, light, and thin" characteristics of electromagnetic wave absorbing materials. The present invention provides an innovative technical path for preparing materials with excellent electromagnetic wave attenuation performance by combining the method of controlling the content of the vulcanizing agent with sulfur atom doping. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1-2 This is a SEM image of sulfur atom-doped coal tar pitch-based carbon aerogel microspheres prepared in Example 1.

[0028] Figure 3 This is the FT-IR image of sulfur atom-doped coal tar pitch-based carbon aerogel microspheres prepared in Example 1.

[0029] Figure 4 This is the XRD diagram of sulfur atom-doped coal tar pitch-based carbon aerogel microspheres prepared in Example 1.

[0030] Figure 5 This is the S2p orbital XPS graph of sulfur atom-doped coal tar pitch-based carbon aerogel microspheres prepared in Example 1.

[0031] Figure 6 This is the nitrogen adsorption / desorption curve of the sulfur atom-doped coal pitch-based carbon aerogel microspheres prepared in Example 1.

[0032] Figure 7 This is a 2D reflection loss diagram of sulfur atom-doped coal tar pitch-based carbon aerogel microspheres prepared in Example 1.

[0033] Figure 8 It is the relationship between the matching thickness and the frequency and the impedance matching relationship diagram of the sulfur atom-doped coal pitch-based carbon aerogel microspheres in Example 1 calculated by the λ / 4 model. DETAILED DESCRIPTION

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.

[0035] The present invention notes that by doping sulfur atoms in carbon aerogel, a large number of CS / C=S functional groups can be formed inside the material. These functional groups act as dipole centers, which enhance the dipole polarization of the carbon aerogel, while increasing the defect concentration and strengthening the interface polarization, thereby further improving the polarization loss of the material to electromagnetic waves.

[0036] The present invention proposes a method for preparing sulfur atom-doped coal pitch-based carbon aerogel, as follows:

[0037] (1) Coal tar pitch (i.e., coal tar pitch) is dissolved in a solvent, a crosslinking agent and a catalyst are added, and the mixture is uniformly mixed to obtain a mixed asphalt solution, the mixed asphalt solution is heated in an oil bath for reaction, and the coal tar-based aerogel microspheres are obtained after washing and drying.

[0038] The role of the solvent is to dissolve the coal tar pitch, and preferably a solvent with strong solubility for coal tar pitch is used, such as one or more of toluene, acetic acid, carbon disulfide, carbon tetrachloride and cyclohexane. Preferably, the ratio of the solvent volume to the coal tar pitch mass is 1 to 15 mL / g.

[0039] The cross-linking agent includes one or more of glyoxal, terephthalaldehyde, terephthalol and furfural. Preferably, the volume ratio of the cross-linking agent to the mass of the coal tar is 5 to 15 mL / g.

[0040] The catalyst comprises one or more of concentrated sulfuric acid, anhydrous aluminum chloride, anhydrous zinc chloride and sodium methoxide. Preferably, the mass ratio of the catalyst to the coal tar pitch is 0.5-8%.

[0041] In step (1), the temperature of the oil bath heating reaction is 50 to 80° C., and the reaction time is 24 to 216 hours.

[0042] In step (1), the washing reagent includes one or both of water and ethanol; the drying temperature is 50 to 160° C., and the drying time is 3 to 32 hours.

[0043] (2) The coal tar pitch-based aerogel microspheres are evenly mixed with the sulfur-containing material to obtain a carbonized precursor.

[0044] The sulfur-containing material includes one or more of sulfur, sulfite and organic sulfur compounds. Specifically, the sulfur-containing material includes one or more of sublimated sulfur, sodium sulfite, thioacetamide and thiourea. The mass ratio of the sulfur-containing material to the coal tar-based aerogel microspheres is (0.1-5):1.

[0045] (3) The carbonized precursor is subjected to carbonization pyrolysis treatment to obtain sulfur atom-doped coal tar pitch-based carbon aerogel microspheres with a size of 50 to 100 nm.

[0046] In step (3), the temperature of carbonization pyrolysis is 800 to 1600° C.; the time of carbonization pyrolysis is 60 to 180 minutes.

[0047] In step (3), the carbonization pyrolysis process is carried out in an oxygen-free atmosphere. Preferably, the carbonization pyrolysis atmosphere includes one or more of a nitrogen atmosphere, an argon atmosphere and a carbon dioxide atmosphere.

[0048] More preferably, in step (3), the heating rate of the carbonization pyrolysis process is also controlled, specifically, the heating rate is 2 to 5° C. / min.

[0049] In the present invention, the type of coal tar is not limited. The present invention performs carbonization and cracking treatment on the carbonization precursor at high temperature, which effectively removes some impurities in the material, and also enhances the mobility of the polymer molecular chain links in the carbonization precursor, protects the network macromolecular 3D structure produced by cross-linking, and thus enhances the structural stability of the coal tar-based carbon aerogel. More importantly, the material obtained by the carbonization pyrolysis temperature treatment has a low degree of graphitization, which helps to control the conductivity of the sulfur atom-doped coal tar-based carbon aerogel, avoid a sharp increase in conductivity due to an excessively high degree of graphitization, prevent impedance matching imbalance, and ensure the performance stability and reliability of the material in electromagnetic wave attenuation applications.

[0050] The present invention notes that by doping with sulfur atoms, a large number of CS / C=S functional groups can be formed in the coal tar pitch-based carbon aerogel. These functional groups act as dipole centers, which enhance the dipole polarization, are beneficial to increase the defect concentration, strengthen the interface polarization, and further enhance the polarization loss of coal tar pitch-based carbon aerogel to electromagnetic waves. However, the amount of sulfur atom doping needs to be precisely controlled. For example, when the amount of sulfur atom doping is too high, it may reduce the overall conductivity of the material, thereby reducing the conductivity consumption. The present invention precisely controls the content of sulfur-containing materials, moderately reduces the overall conductivity of the material, thereby reducing its conductivity, and maintaining the necessary conductivity loss, thereby achieving impedance matching and optimization of electromagnetic wave absorption performance. In addition, sulfur atom doping is also beneficial to inducing larger pores in the mesh structure, thereby significantly increasing the specific surface area of ​​the material (≥500m 2 / g). During the carbonization and cracking process, the melting effect of sulfur-containing materials can serve as a flow template, further promoting the increase of specific surface area.

[0051] The advantage of sulfur atom doping is not only to optimize the pore structure of the material, but also to enhance the multiple reflections and interface polarization of electromagnetic waves inside the material, effectively improving the material's attenuation ability to electromagnetic waves. The sulfur atom-doped coal tar-based carbon aerogel material prepared by the present invention has a minimum reflection loss of -69.52 dB, an effective absorption bandwidth greater than 4 GHz, and a maximum bandwidth of 5.44 GHz.

[0052] The technical solution of the present invention is described in detail below with specific embodiments.

[0053] Example 1

[0054] 5 g of coal tar, 50 mL of furan formaldehyde, a cross-linking agent, 10 mL of solvent (calculated by volume ratio, toluene: acetic acid = 1:1), and 1 mL of concentrated sulfuric acid, a catalyst, were placed in a three-necked flask and mixed. The flask was placed in a 70°C water bath and reacted for 96 hours to fully gelate to obtain coal tar-based aerogel microspheres. The obtained coal tar-based aerogel microspheres were cooled to room temperature, placed in an oven at 100°C, and dried for 5 hours.

[0055] 1 g of coal tar-based aerogel microspheres and 0.5 g of sublimated sulfur were thoroughly mixed in an agate mortar and transferred to a porcelain boat, which was then placed in a tubular furnace for calcination. Under a nitrogen atmosphere, the temperature was raised to 900 °C at a rate of 5 °C / min and maintained for 2 h to obtain the final product, namely sulfur atom-doped coal tar-based carbon aerogel microspheres.

[0056] The prepared sulfur atom-doped coal pitch-based carbon aerogel microspheres and sliced ​​paraffin were heated and fully mixed at a mass ratio of 2:8 to obtain concentric rings with an outer diameter of 7 mm and an inner diameter of 3.04 mm. Electromagnetic parameters were measured at a frequency of 2-18 GHz using a vector network analyzer. The measured complex dielectric constant and complex magnetic permeability were calculated to obtain a minimum reflection loss RLmin of -69.52 dB at a thickness of 1.48 mm, and a maximum effective bandwidth of 5.12 GHz.

[0057] Figure 1-2 This is a SEM image of sulfur atom-doped coal tar pitch-based carbon aerogel microspheres prepared in Example 1.

[0058] Figure 3 This is the FT-IR image of sulfur atom-doped coal pitch-based carbon aerogel microspheres prepared in Example 1, with a wave number range of 500-3500 cm -1 ,Depend on Figure 1 It can be seen that after the cross-linking reaction, the stretching vibration peak of the C=O bond of the furfural (furfural) molecule in the infrared spectrum of the obtained carbon aerogel gradually disappeared, but the characteristic vibration absorption peak of the heteropentacyclic ring was still retained, indicating that a cross-linking reaction occurred between coal tar pitch and furfural, and the reaction was carried out according to the experimental design.

[0059] Figure 4 is the XRD pattern of sulfur atom-doped coal pitch-based carbon aerogel microspheres prepared in Example 1. Figure 2 It can be seen that only one set of peaks appears in XRD, which are the diffraction peaks of amorphous carbon.

[0060] Figure 5 The S2p orbital XPS image of sulfur-doped coal-tar pitch-based carbon aerogel microspheres effectively proves that the sulfur atoms have been successfully doped into the interior of the material.

[0061] Figure 6 The nitrogen adsorption / desorption curve of the sulfur atom-doped coal tar pitch-based carbon aerogel microspheres prepared in Example 1 is an obvious type I isotherm. The BET specific surface area is calculated to obtain a specific surface area of ​​the sulfur atom-doped coal tar pitch-based carbon aerogel microspheres of 995 m 2 / g.

[0062] Figure 7 It is the 2D reflection loss of the sulfur atom-doped coal tar pitch-based carbon aerogel microspheres prepared in Example 1. Specifically, when the thickness is 1.48 mm, the strongest reflection absorption is -65.92 dB at 15.25 GHz, which shows that the above material has good wave absorbing performance.

[0063] Figure 8 The relationship between the matching thickness and frequency and the impedance matching relationship diagram of the sulfur atom-doped coal pitch-based carbon aerogel microspheres prepared in Example 1 calculated by the λ / 4 model are shown in FIG. 1. At 15.42 GHz, Z0 / Z in The value of is 1, that is, the impedance of free space and the impedance of the material are well adapted, so that the electromagnetic wave can fully enter the interior of the material to achieve multiple reflections and attenuation; and the λ / 4 model is basically consistent with the actual results, indicating that sulfur atoms doped coal pitch-based carbon aerogel microspheres are effective materials for electromagnetic wave absorption.

[0064] In summary, the sulfur atom-doped coal tar pitch-based carbon aerogel microspheres prepared in this embodiment have high electromagnetic wave absorption performance and good stability. Therefore, the sulfur atom-doped coal tar pitch-based carbon aerogel microspheres of the present invention have ideal development prospects in the field of electromagnetic wave absorption.

[0065] Example 2

[0066] 5 g of coal tar, 50 mL of cross-linking agent p-toluene glycol, 5 mL of solvent (calculated by volume ratio, toluene: acetic acid = 1:1), and 0.4 g of catalyst anhydrous aluminum chloride were placed in a three-necked flask and mixed. The flask was placed in an 80°C water bath and reacted for 216 hours to fully gelate to obtain coal tar-based aerogel microspheres. After the obtained coal tar-based aerogel microspheres were cooled to room temperature, they were placed in an oven at 160°C and dried for 32 hours.

[0067] 1 g of coal tar-based aerogel microspheres and 5 g of sublimated sulfur were fully mixed in an agate mortar, transferred to a porcelain boat, and placed in a tubular furnace for calcination. In a nitrogen atmosphere, the temperature was increased to 1600°C at a rate of 5°C / min and maintained for 3 h to obtain the final product.

[0068] The prepared sulfur atom-doped coal pitch-based carbon aerogel microspheres and sliced ​​paraffin were heated and fully mixed at a mass ratio of 2:8 to obtain concentric rings with an outer diameter of 7 mm and an inner diameter of 3.04 mm. Electromagnetic parameters were measured at a frequency of 2-18 GHz using a vector network analyzer. The measured complex dielectric constant and complex magnetic permeability were calculated to obtain a minimum reflection loss RLmin of -57.66 dB at a thickness of 1.98 mm, and a maximum effective bandwidth of 4.12 GHz.

[0069] Example 3

[0070] 5 g of coal tar, 50 mL of furan formaldehyde, a cross-linking agent, 5 mL of solvent (calculated by volume ratio, toluene: acetic acid = 1:1), and 0.5 mL of concentrated sulfuric acid as a catalyst were placed in a three-necked flask and mixed. The flask was placed in a 50°C water bath and reacted for 24 hours to fully gelate to obtain coal tar-based aerogel microspheres. The obtained coal tar-based aerogel microspheres were cooled to room temperature, placed in an oven at 50°C, and dried for 3 hours.

[0071] 1 g of coal tar-based aerogel microspheres and 0.1 g of sublimated sulfur were fully mixed in an agate mortar, transferred to a porcelain boat, and placed in a tubular furnace for calcination. In a nitrogen atmosphere, the temperature was increased to 800 °C at a rate of 2 °C / min and maintained for 1 h to obtain the final product.

[0072] The prepared sulfur atom-doped coal pitch-based carbon aerogel microspheres and sliced ​​paraffin were heated and fully mixed at a mass ratio of 2:8 to obtain concentric rings with an outer diameter of 7 mm and an inner diameter of 3.04 mm. Electromagnetic parameters were measured at a frequency of 2-18 GHz using a vector network analyzer. The measured complex dielectric constant and complex magnetic permeability were calculated to obtain a minimum reflection loss RLmin of -60.93 dB at a thickness of 1.85 mm, and a maximum effective bandwidth of 4.07 GHz.

[0073] Example 4

[0074] 5 g of coal tar, 50 mL of furan formaldehyde, a cross-linking agent, 10 mL of solvent (calculated by volume ratio, toluene: acetic acid = 1:1), and 1 mL of concentrated sulfuric acid, a catalyst, were placed in a three-necked flask and mixed. The flask was placed in a 70°C water bath and reacted for 96 hours to fully gelate to obtain coal tar-based aerogel microspheres. The obtained coal tar-based aerogel microspheres were cooled to room temperature, placed in an oven at 100°C, and dried for 5 hours.

[0075] 1 g of coal tar-based aerogel microspheres and 1.5 g of thioacetamide were thoroughly mixed in an agate mortar and transferred to a porcelain boat, which was then placed in a tubular furnace for calcination. Under a nitrogen atmosphere, the temperature was raised to 900 °C at a rate of 5 °C / min and maintained for 2 h to obtain the final product, namely sulfur atom-doped coal tar-based carbon aerogel microspheres.

[0076] The prepared sulfur atom-doped coal tar-based carbon aerogel microspheres and sliced ​​paraffin wax were heated and fully mixed at a mass ratio of 2:8 to obtain concentric rings with an outer diameter of 7 mm and an inner diameter of 3.04 mm. Electromagnetic parameters were measured at a frequency of 2-18 GHz using a vector network analyzer. The measured complex dielectric constant and complex magnetic permeability were calculated to obtain a minimum reflection loss RLmin of -47.54 dB at a thickness of 2.77 mm, and a maximum effective bandwidth of 4.29 GHz.

[0077] Comparative Example 1

[0078] 5 g of coal tar, 50 mL of furan formaldehyde, a cross-linking agent, 10 mL of solvent (calculated by volume ratio, toluene: acetic acid = 1:1), and 1 mL of concentrated sulfuric acid as a catalyst were placed in a three-necked flask and mixed. The flask was placed in a 70°C water bath for reaction for 96 hours to fully gelate the coal tar-based aerogel microspheres. The obtained coal tar-based aerogel microspheres were cooled to room temperature, placed in an oven at 100°C, and dried for 5 hours. 1 g of coal tar-based aerogel microspheres was placed in a tubular furnace for calcination. Under nitrogen, the temperature was increased to 900°C at a heating rate of 5°C / min and maintained for 2 hours to obtain the final product, coal tar-based carbon aerogel microspheres.

[0079] The coal tar-based carbon aerogel microspheres prepared in the comparative example were heated and fully mixed with sliced ​​paraffin at a mass ratio of 2:8 to obtain concentric rings with an outer diameter of 7 mm and an inner diameter of 3.04 mm. Electromagnetic parameters were measured at a frequency of 2-18 GHz using a vector network analyzer. The measured complex dielectric constant and complex magnetic permeability were calculated to obtain a minimum reflection loss RLmin of -7.27 dB at a thickness of 3.75 mm, with no effective bandwidth.

[0080] Comparative Example 2

[0081] Compared with Example 2, the sulfur atoms in this comparative example are excessively doped, that is, the amount of sublimated sulfur is 6 g (the mass ratio of sublimated sulfur to coal tar pitch-based aerogel is 6:1), and the other conditions are the same as those in Example 1.

[0082] The material prepared in Comparative Example 2 was subjected to electromagnetic parameter measurement in the manner described in Example 1, and the measured complex dielectric constant and complex magnetic permeability were calculated to obtain a minimum reflection loss RLmin of -30.25 dB at a thickness of 4.54 mm, with no effective bandwidth. Excessive doping of sulfur atoms will cause a sudden drop in its conductivity, thereby affecting the imbalance of the impedance matching between the internal material and the impedance of free space, and the conductive network is destroyed, weakening the conductivity loss.

[0083] The embodiments provided by the present invention are described in detail above. Specific examples are used herein to describe the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing sulfur atom-doped coal pitch-based carbon aerogel, characterized in that: include: (1) dissolving coal tar pitch in a solvent, adding a crosslinking agent and a catalyst, and mixing them uniformly to obtain an asphalt mixed solution, heating the asphalt mixed solution to react, and washing and drying to obtain coal tar pitch-based aerogel microspheres; (2) uniformly mixing the coal tar pitch-based aerogel microspheres and the sulfur-containing material to obtain a carbonized precursor; Wherein, the mass ratio of sulfur-containing material to coal tar pitch-based aerogel microspheres is (0.1-5):1; (3) The carbonized precursor is subjected to carbonization pyrolysis treatment in an oxygen-free atmosphere to obtain sulfur-doped coal tar pitch-based carbon aerogel microspheres.

2. The method for preparing sulfur atom-doped coal pitch-based carbon aerogel according to claim 1, characterized in that: In step (2), the sulfur-containing material includes one or more of elemental sulfur, sulfite and organic sulfur compound. Preferably, the sulfur-containing material includes one or more of sublimated sulfur, sodium sulfite, thioacetamide and thiourea.

3. The method for preparing sulfur atom-doped coal pitch-based carbon aerogel according to claim 1, characterized in that: In step (3), the temperature of carbonization pyrolysis is 800 to 1600° C., and the time of carbonization pyrolysis is 60 to 180 minutes.

4. The method for preparing sulfur atom-doped coal pitch-based carbon aerogel according to claim 3, characterized in that: In step (3), the heating rate of the carbonization pyrolysis process is controlled to be 2 to 5°C / min.

5. The method for preparing sulfur atom-doped coal pitch-based carbon aerogel according to any one of claims 1 to 4, characterized in that: In step (1), the solvent includes one or more of toluene, acetic acid, carbon disulfide, carbon tetrachloride and cyclohexane; The ratio of the solvent volume to the coal tar pitch mass is 1 to 15 mL / g.

6. The method for preparing sulfur atom-doped coal pitch-based carbon aerogel according to any one of claims 1 to 4, characterized in that: The cross-linking agent includes one or more of glyoxal, terephthalaldehyde, terephthalenedimethanol and furanaldehyde; The ratio of the volume of the cross-linking agent to the mass of the coal tar is 5 to 15 mL / g.

7. The method for preparing sulfur atom-doped coal pitch-based carbon aerogel according to any one of claims 1 to 4, characterized in that: The catalyst includes one or more of concentrated sulfuric acid, anhydrous aluminum chloride, anhydrous zinc chloride and sodium methoxide; The mass ratio of the catalyst to the coal tar pitch is 0.005-0.

08.

8. The method for preparing sulfur atom-doped coal pitch-based carbon aerogel according to any one of claims 1 to 4, characterized in that: In step (1), the heating reaction temperature is 50-80°C, and the reaction time is 24-216 hours; the drying temperature is 50-160°C, and the drying time is 3-32 hours.

9. A sulfur atom-doped coal pitch-based carbon aerogel, characterized in that: The carbon aerogel is prepared by the method for preparing the sulfur atom-doped coal tar pitch-based carbon aerogel according to any one of claims 1 to 8.

10. An application of sulfur atom-doped coal pitch-based carbon aerogel, characterized in that: The sulfur atom-doped coal tar pitch-based carbon aerogel prepared by the method for preparing the sulfur atom-doped coal tar pitch-based carbon aerogel described in any one of claims 1 to 8 is made into an electromagnetic wave absorbing material and used in the field of electromagnetic wave absorption.

Citation Information

Patent Citations

  • Preparation method of carbon aerogel

    CN113816357A

  • Porous carbon wave-absorbing material as well as preparation method and application thereof

    CN115594162A

  • Preparation method of magnetic particle doped coal pitch-based porous carbon wave-absorbing material

    CN118125417A

  • Cerium oxide sulfur-doped carbon aerogel microsphere, preparation method therefor and application thereof

    WO2024108743A1